PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN MASYARAKAT MENJADI PELANGGAN PDAM SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Mursyid Mursyid; Muhammad Fatkhurohman Albashori (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
The purpose of this study was to determine 1) the influence of the product on the community decision to become a customer of PDAM Sleman DIY, 2) the influence of price on the community decision to become a customer of PDAM Sleman DIY, 3) the influence of distribution on the community decision to become a customer of PDAM Sleman DIY, 4) the effect of promotion on the community decision to become a customer of PDAM Sleman DIY, and 5) the effect of the curious mix consisting of product, price, distribution and promotion simultaneously on the community decision to become a customer of PDAM Sleman DIY. The results of the study concluded that 1) The product has a significant influence on customer decisions of PDAM Sleman. This is evidenced by the t arithmetic value of 6.471, 2) Price has a significant influence on customer decisions of PDAM Sleman. This is evidenced by the t-count value of 3.157, 3) Distribution has a significant influence on customer decisions of PDAM Sleman. This is evidenced by the t value of 7.033, 4) Promotion has a significant influence on customer decisions of PDAM Sleman. This is evidenced by the value of t count of 5.173, and 5) Product, price, distribution and promotion together have a significant influence on customer decisions of PDAM Sleman. This is evidenced by the calculated F value of 74,316.